Study on impact properties of arenga pinnata fibre reinforced epoxy composites - Leman, Z.; Sastra, H. Y.; Sapuan, S. M.; Hamdan, M. M.; Maleque, Md. Abdul (PATRI, 2005)
Natural fibre composites have gained their importance in the recently in some non-structural and semi-structural components in engineering due to their acceptable strength and stiffness in addition to their low cost, abundance and renewable. A study on impact properties of arenga pinnata fibre reinforced epoxy composites is presented in this paper.